A Future Trend for Science Education: A Constructivism-Humanism Approach to Trans-Contextualisation - Jack Holbrook; T. B. M. Chowdhury; Miia Rannikmäe (MDPI AG, 2022)
Today's society faces new challenges, especially related to sustainability, in which the role of science within society is becoming increasingly important. This study seeks to re-examine the focus of school science/STEM education in light of increasing societal challenges by introducing a trans-contextualisation component within science education so as to go beyond the classroom and seek to impact the societal setting. In so doing, this study, through a constructivism-humanism approach, develops a theoretical 4-phase model by adding a trans-contextualisation learning phase to a literature-supported 3-stage science education teaching model. This enhanced model is put forward to enable science education to play a stronger role in impacting societal development towards building an active informed citizenry, enabling society to reflect on potential ways to meet its needs in moving towards a sustainable future. The study seeks science educator views familiar with the 3-stage teaching approach on the enhanced 4-phase model in terms of its value, feasibility and potential constraints. Such views are shown to be positive and aligned with the generally supportive views of teachers identified in a prior study.